EFFECT OF BIO AND CHEMICAL FERTILIZERS ON SOIL PROPERTIES, YIELD ATTRIBUTES AND YIELD OF BABY CORN (ZEA MAYS L.) - EUGENIA P. LAL, DHARMENDRA MISHRA AND (The Bioscan, 2016)
An experiment was conducted at the research field department of biological sciences sam higginbottom institute of agriculture, technology and sciences, (deemed university) Allahabad, 211007 (U.P). India, during seasons of 2014 -15 to investigate the effect of different bio and chemical fertilizers on soil properties, Yield attributes and Yield of Baby corn with the aim to maintain the soil properties, increase the yield and nutrient value of baby corn by different biofertilizers. The variety sonal F1 hybrid was used as experimental material and treatments consisted of various combinations of biofertilizers Azotobacter chroococcum, Pseudomonas putida, Bacillus mucilaginosus and N.P.K fertilizers. Biofertilizers significantly increased soil properties, yield and yield attributing characters. The best treatment identified was based on the mean performance the treatment 6 (@ 50% RDN Pseudomonas putida + Azotobacter chroococcum 20g kg-1). Inter action effect of biofertilizers was significant for all character except for potassium. Thus, it indicates that the process of biofertilizers may be better option for soil properties, and yield component of baby corn.